Anthropometric characteristics are highly correlated with anaerobic power in male handball and soccer players - Zeynep Inci Karadenizli; Huseyin Ozkamcı; Raif Zileli (ROL Spor Bilimleri Dergisi)
The purpose of this research is to examine the relationship between anthropometric characteristics and anaerobic power of volunteer male athletes. Male athletes in the college soccer and handball teams (n: 20; age: 23.20±1.94 years; height: 179.81±7.96cm; weight: 79.50±9.23kg) volunteered for the study. For anthropometric characteristics, some measurements (body height, arm span, hand length, and chest, waist, arm, thigh and leg circumferences) were taken. Vertical jump height via Countermovement Jump (CMJ) test and body weight were also measured. Anaerobic power value was obtained using Lewis formula. For statistical analysis, descriptive statistics and Pearson correlation analyses were performed using the SPSS 17.00 package program. Significance value was set as p<0.05. There found a positive correlation between anaerobic power values ​​and the values of body height (r=.660), body weight (r=0.912), arm span (r=0.547), dominant hand length (r=0.578), upper arm circumference (relaxed) (r=0.690), upper arm circumference (flexed) (r=0.689), thigh circumference (r=0.643), calf circumference (r=0.533), waist circumference (r=0.826), chest circumference (r=0.704), vertical jump height (r=0.493).​​ The results showed that there was a statistically significant and high correlation between all measured anthropometric characteristics and anaerobic power values. Therefore, it is recommended trainers pay attention to these characteristics in player selection, training plans and determining performance of athletes.